2013
DOI: 10.5489/cuaj.1246
|View full text |Cite
|
Sign up to set email alerts
|

Middle calyx access in complete supine percutaneous nephrolithotomy

Abstract: Background: Middle calyx access has been underused in percutaneous nephrolithotomy (PCNL), especially in the supine position. We compared the safety and efficacy outcomes between middle calyx and lower calyx accesses in the complete supine PCNL in a non-randomized single-surgeon clinical study. Methods: Between February 2008 and October 2011, 170 patients underwent posterior subcostal single tract complete supine PCNL with one-shot dilation and middle calyx (n = 48) and lower calyx (n = 122) accesses. Stone lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In their study, Song et al (12) indicated that the mean operative time was shorter in middle calyx access patients when compared lower and upper calyx access patients. In their study related to supine position, Falahatkar et al (18) indicated that the mean operative time in patients who underwent middle calyceal access PCNL was shorher than those undergoing lower calyceal access PCNL (12). On the other hand, the mean operative time in the study of Aron et al (16) were 48 and 74 minutes in upper and lower calyx access respectively (16).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their study, Song et al (12) indicated that the mean operative time was shorter in middle calyx access patients when compared lower and upper calyx access patients. In their study related to supine position, Falahatkar et al (18) indicated that the mean operative time in patients who underwent middle calyceal access PCNL was shorher than those undergoing lower calyceal access PCNL (12). On the other hand, the mean operative time in the study of Aron et al (16) were 48 and 74 minutes in upper and lower calyx access respectively (16).…”
Section: Discussionmentioning
confidence: 97%
“…In their study, Song et al (12) found a significantly higher stone-free rate in middle pole access group. Falahatkar et al (18) showed that stone-free rate was higher in middle calyceal access patients than in lower calyceal access patients. In this study, stone-free rate was found to be similar between the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Related with this issue, while in their original study, Song et al [17] found the procedural duration to be significantly shorter in the middle pole access group compared with upper pole and lower pole accesses. Last but not least, by comparing the operative durations between middle calyceal and lower calyceal approaches, Falahatkar et al [18] were able to show that the operative time was significantly shorter in the middle calyx group than in the lower calyx group (60.7 vs. 80.1 min, respectively) and that there was no statistically significant difference in Hb reduction rates, blood transfusion requirement, and complication rates between the 2 puncture sites.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the possible reasons for such a higher success rate obtained from middle calyceal access, the authors stated well that the quick, practical access via the middle calyx, establishment of a proper angle between the middle calyx tract and long axis of the kidney, and optimal alignment of the access with the ureteropelvic junction could be among the possible factors considered. Last but not least "although not as significant as the success rates," the complication rates were also found to be limited during middle calyceal access where excessive torquing of the rigid nephroscope against the pelvicalyceal system to reach an inaccessible calyx has been reported to be the most important cause of bleeding during PNL [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Although some studies have advocated easy approach into upper calyceal stones through middle calyx, this route of access is not generally preferred. [7] In this study, we investigated patients who underwent PNL operation in our clinic because of isolated calyceal stones using a single access site at the same location. In our study, we aimed to evaluate the impact of single calyceal access performed in our clinic targeted at the calyceal location of the stone on PNL success, and complication rates in cases with isolated renal stones.…”
Section: Introductionmentioning
confidence: 99%